A articulação do adjetivo nas formações nominais: Uma abordagem sintática de bases enunciativas - Igor Caixeta Trindade Guimaraes (2017)
This work discusses aspects of the adjective syntax in nominal formations, based on an enunciative approach. In particular, it deals with relations of dependence between noun and adjective, analyzed from a historical point of view. To do so, it uses three central notions. The first of these is the notion of discursiveness, through which it is argued thatthe sense effects that the adjective adds to the noun must be understood in a discursive instance that is sometimes less complex, sometimes more complex. A complex occurrence is the black consciousness nominal formation, in which the adjective does not characterize or qualify consciousness, but evokes a social fabric that can be summarized in terms of the awareness of the Brazilian society regarding the valorizationof the black, in the context of combating racism. The second notion is that of referential, which refers to the point of view of the reference that sustains the objects of discourse. By way of example, the following statements are: (1) Black man kidnaps a child in East Zone of BH and (2) Know the new names of international black music.The presence of the adjective, in these two occurrences, is not determined properly by the name (man / music) to which it is added, but by the historical relations that support the statements. To discuss them, an adjective deletion test can be applied. In (1), this deletion would produce a silencing of racism; in (2), would produce a silencing of theaffirmation of otherness. The thesis defended in this research is that the references determine the articulation of the adjective. In (1), the absence of the adjective would not prejudice the statement if it is not supported by an ethnic referential. In (2), differently, the absence of the adjective would compromise the utterance, if its referential is related to affirmative actions. The third notion underlying the research is that of enunciativepertinence, by which it is analyzed that the frequency with which certain adjectives associate to some names more than to others is due to a memory of enunciations, and not to the requirement of completeness of meaning of the name, for each statement.